On the diazonium surface treatment of graphene oxide: effect on thermoelectric behavior of polythiophene hybrid ternary composites - Metref, Lynda; Mekki, Ahmed; Bekkar Djeloul Sayah, Zakaria; Nedjar, Lynda; Delaleux, Fabien; Durastanti, Jean-Felix; Riou, Olivier (Polymer bulletin (Berlin, Germany), 2023)
Nowadays, thermoelectric materials are the subject of huge number of research dealing with energy conversion optimization. Herein, we report the study of thermoelectric performance improvement of three different ternary hybrid composite-based polythiophene, poly(3,4-ethylene-dioxythiophene)/poly(4-styrenesulfonate) and both of graphene oxide, reduced graphene oxide and aryl diazonium salt functionalized graphene oxide (FGO). Structural and morphological characterization of the as-prepared materials was carried out by using FTIR, Raman spectroscopy and SEM. Thermoelectric characteristics were determined through the measurement of figure of merit ZT and the electrical conductivity as well as the Seebeck coefficient at room temperature of 298.15 K. Hybrid composite based on functionalized graphene oxide (PTh-FGO-PEDOT:PSS) has shown the most significant improvement over polythiophene alone, marking an enhancement of 71 times in terms of electrical conductivity and 3 times in terms of Seebeck coefficient, resulting in very large ZT coefficient value within magnitude of 2.3 × 10 5 , which highlights the great apport of using aryl diazonium salts in surface modification of graphene oxide.